Some problems of determining diversification level of enterprise activities - Ginevičius, Romualdas; Petraškevičius, Vladislavas (Business: Theory and Practice, 2008)
Various methods of measuring diversification of enterprise activities have been suggested. This shows that any unified approach to solving this significant theoretical and practical problem can hardly be found now. One of the main reasons for this is that the reliable analysis of diversification processes, aims and effects on various aspects of enterprise activities has not been performed yet. As shown by the present investigation, diversification criteria defining the number of areas of activities rather than the criteria describing the variation of work volumes in these areas should be taken into consideration.Article in Lithuanian.Įmonių veiklos diversifikacijos matavimo problematikaSantrauka. Įmonių veiklos diversifikaciją matuoti siūloma įvairiais būdais. Tai liudija, kad dar nėra vieningo požiūrio į šį svarbų teorijai ir praktikai klausimą. Skirtingų požiūrių į diversifikacijos matavimą viena iš pagrindinių priežasčių yra ta, kad mažai remiamasi diversifikacijos procesų esmės, tikslų, poveikio įmonių veiklos įvairiems aspektams analize. Iš tyrimų aiškėja, kad diversifikacijos rodikliai visų pirma turi pabrėžti veiklos sričių skaičių, o ne darbų apimčių variaciją tarp jų.Reikšminiai žodžiai: įmonių veiklos diversifikacija, diversifikacijos matavimas.First published online: 19 Sep 2008